Pengaruh Berat Karbon Aktif Dari Ampas Tebu dan Lama Perendaman Terhadap Kualitas Minyak Goreng Bekas - Mardwita; Eka Sri Yusmartini; Nindia Selviana (Jurnal INOVATOR, 2022)
The amount of used cooking oil is increasing along with human activities. Used cooking oil that is disposed directly into the environment will give a negative impact on health and the quality of the environment, therefore it is necessary to purify the used cooking oil so that the used cooking oil can be reused. In this study, used cooking oil that has been used with heating time of 3 hrs, 5 hrs, and 7 hrs was used. The used cooking oil was purified using activated carbon made from 100 mesh bagasse with variations in weight of 2.5 g, 5 g, and 7 g, soaking time of activated carbon in used cooking oil were 24 hrs, 48 ​​hrs, and 72 hrs. The analysis used is the analysis of water content, free fatty acid content, and the amount of saponification. The results showed that the water content and saponification rate decreased with the length of contact time and the weight of activated carbon. The lowest free fatty acid content was produced when using activated carbon 7.5 g and contact time for 24 hrs.